Penggunaan Metode Diskusi Untuk Meningkatkan Hasil Hasil Siswa Kelas VII Pada Mata Pelajaran PAI di UPTD SMPN 2 Kecamatan Lareh Sago Halaban - Diska Monalisa; Zulfani Sesmiarni; Rodi Rodi; Meyriza Hamda; Desri Wahyuni; Yona Widia Eka Putri (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This research is motivated by the low learning outcomes of Islamic Religious Education students in class SMPN 2 Lareh Sago Halaban District. Differentiated learning in the most appropriate and accurate learning in conveying messages and will greatly help students' understanding of the discussion method. The purpose of this study was to: determine the increase in students' Islamic Religious Education (PAI) learning outcomes through the discussion method in class SMPN 2 Lareh Sago Halaban District. Data collection techniques used were tests and observations. The results showed that the discussion method in the PAI subject was able to increase students' learning motivation, especially class VII students of kelas SMPN 2 Kecamatan Lareh Sago Halaban. Quantitative evidence can be seen from the increase in the motivation variable test from the first meeting and the second meeting. From the test results, there was also an increase from the pre-action results of 45%, in cycle I (first) it increased to 60%, in cycle II (second) it also increased to 90%. While qualitative evidence can be explained from the number of students who expressed their pleasure in the use of this video media, the growth of motivation, student concentration on the PAI subject.